Dampak Penggunaan Gadget Terhadap Perubahan Kebiasaan Belajar Siswa Kelas IV SD Islam Siti Sulaechah 2 Sriwulan Sayung Demak Tahun Ajaran 2022 - Dianti Widiastuti; Diana Endah Handayani; Kiswoyo Kiswoyo (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The background that drives this research is that due to the habit of daring to study using gadgets during a pandemic, it is found that the impact of gadgets on changes in fourth grade study habits. This study uses an approach, using a descriptive method. The data in this study were obtained through the distribution of questionnaires, interviews and documentation. The results of the questionnaire analysis on students' use of gadgets showed that the percentage of answers was always 38%, often 6%, sometimes 19% and never 36%. And in the habit of student learning questionnaires, the percentage of answers always showed that 27% answered always, 9% answered often, 20% answered sometimes, and 44% answered never. It was concluded that there was an impact of using gadgets on changes in students' study habits. The data in this study were obtained through the distribution of questionnaires, interviews and documentation.